Sistem Informasi Reservasi dan Pembayaran Tagihan Hotel Menggunakan Payment Gateway - Parasian D.P Silitonga; Evinri Mentari Parhusip (Jurnal ICT: Information Communication & Technology, 2022)
Hotel Reservation and Bill Payment Information System using Payment Gateway, is an information system that focuses on reservation data and payment systems using payment gateways entered by receptionists in business transactions. In the previous system, data was entered manually by taking notes in the guest book or agenda book. The risk is less effective and efficient management. Using a web[1]based information system, the input data of each transaction can be recapitulated quickly. Therefore, a website-based recording system is needed to improve the efficiency of the work system in hotels. The development of this system aims to help manage reservation and payment data more effectively and efficiently, so that transactions are recorded and stored properly. The system is created using the SDLC Waterfall method, which includes analysis of system needs, system design, system implementation, system testing and system maintenance. Website-based system, using PHP programming language with Laravel framework, Sublime Text editor, and Xampp as localhost, MySql Database. The existence of a web-based information system will overcome errors in the recording process manually and make it easier to make reports related to reservations for the finalization of computerized transaction data automatically.